TARI WALI BARIS BUGBUG DI PURA DALEM GEDE SELAUNGAN KECAMATAN BANGLI KABUPATEN BANGLI - Suarjata, Ida Bagus Ketut; Girinata, I Made; Pradnya, I Made Adi Surya (UHN IGB Sugriwa Denpasar, 2023)
ABSTRACT The Baris Bugbug wali dance is different from the Baris dance in general, where in general the Baris dance is used as a complement to a ritual, but the uniqueness of the Baris Bugbug wali dance is as part of a series of piodalan ceremonial activities at Dalem Gede Selaungan Temple. The Baris Bugbug wali dance is a symbol of the Gandharwa-gandharwi as Ida Bhatara's troop or plan that goes down with Ida Bhatara during the piodalan ceremony. Before the Baris bugbug has been danced, other piodalan ritual activities cannot be continued, after which the Baris Bugbug dance will continue with the offering ritual of offering offerings. The purpose of this study was to determine the relationship between staging and piodalan activities at Dalem Gede Selaungan Temple. This study used a qualitative model, with data sources collected based on observations, literature studies and interviews with informants who were determined by purposive sampling technique. The conclusion of this research is from the formulation of the problem of the existence of the Baris Bugbug wali dance, that is, the entire range of movements and floor patterns of the Baris Bugbug wali dance has the meaning of the process of purifying the universe as the descent of Ida Bhatara's holy energy during the piodalan ceremony. From the formulation of the problem for staging Baris Bugbug, it is found that the stage before the performance is mental strengthening and seriousness to carry out the yadnya ceremony, the staging stage is part of the process of self-purification and jnana kanda to Ida Sang Hyang Widhi. And the finished stage of the performance is the process of releasing negative energy and welcoming positive energy in humans. In the formulation of the problem of the stages of sacralization, the result is that the process of sacralization is carried out on the dancers as a medium for the decline of Ida Bhatara's energy, and the spears and coils are places where Ida Bhatara's sacred energy descends. Keywords: wali dance, bugbug line, presence, staging, sacralization.